Prevalence, isolation and molecular characterization of Bovine Ephemeral Fever Virus in south and southeast regions of Turkey in the outbreak of 2020 - Tokgoz, BS; Tokgoz, EA; Sözmen, MA; Avci, O; Ütük, AE (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study is to investigate the presence of BEF disease in the blood, sera and tissue samples sent to the Viral Diagnosis Laboratory of Adana Veterinary Control Institute with suspected BEF in 2020 from different provinces of Turkey as well as to perform characterization and phylogenetic analysis of cases tested positive with molecular methods. For this purpose, 79 defibrinated blood and 2 tissue samples as well as 168 sera samples obtained from cattle varying in breed, age, and sex, were examined by using Real Time RT-PCR and Blocking ELISA, respectively. Two new degenerate primers amplifying 956 bp of the protein G (AVKEF_AATGTTCCNGTGAATTGTGGAG and AVKER_TGCATAATCYCTTCCTGGTCT) were designed and the phylogenetic analysis of the samples tested positive with RT-PCR was performed. As a result of the examinations conducted, 64.20% (52/81) of the defibrinated blood and tissue samples, and 69.04% (116/168) of the sera samples were diagnosed as positive. Through VERO cell culture, the virus was isolated from the tissue samples of 2 animals in Adana and Sanliurfa provinces, which were positive. The phylogenetic analysis revealed that the virus circulated in Turkey during the 2020 pandemic belongs to the Middle East lineage. We concluded that monitoring the disease and identifying the lineages of the virus that have caused pandemic are significant in the selection of the proper vaccine and the disease control.